Epidemiology and molecular relationships of Cryptosporidium spp. in people, primates, and livestock from Western Uganda. - Stephanie J Salyer; Thomas R Gillespie; Innocent B Rwego; Colin A Chapman; Tony L Goldberg (Public Library of Science (PLoS), 2012)
Cryptosporidium is one of the most common parasitic diarrheal agents in the world and is a known zoonosis. We studied Cryptosporidium in people, livestock, and non-human primates in the region of Kibale National Park, Uganda. Land use change near the park has resulted in fragmented forest patches containing small, remnant populations of wild primates that interact intensively with local people and livestock. Our goal was to investigate risk factors for Cryptosporidium infection and to assess cross-species transmission using molecular methods.Diagnostic PCR revealed a prevalence of Cryptosporidium of 32.4% in humans, 11.1% in non-human primates, and 2.2% in livestock. In the case of humans, residence in one particular community was associated with increased risk of infection, as was fetching water from an open water source. Although 48.5% of infected people reported gastrointestinal symptoms, this frequency was not significantly different in people who tested negative (44.7%) for Cryptosporidium, nor was co-infection with Giardia duodenalis associated with increased reporting of gastrointestinal symptoms. Fecal consistency was no different in infected versus uninfected people or animals. DNA sequences of the Cryptosporidium oocyst wall protein gene placed all infections within a well-supported C. parvum/C. hominis clade. However, the only two sequences recovered from primates in the core of the park's protected area fell into a divergent sub-clade and were identical to published sequences from C. parvum, C. hominis, and C. cuniculus, suggesting the possibility of a separate sylvatic transmission cycle.Cryptosporidium may be transmitted frequently among species in western Uganda where people, livestock, and wildlife interact intensively as a result of anthropogenic changes to forests, but the parasite may undergo more host-specific transmission where such interactions do not occur. The parasite does not appear to have strong effects on human or animal health, perhaps because of persistent low-level shedding and immunity.